2002
DOI: 10.1093/humrep/17.1.92
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of medical abortion and surgical vacuum aspiration at 10-13 weeks gestation

Abstract: Medical abortion is safe and effective at 10-13 weeks gestation and should be considered an option for those women who wish to avoid surgery and anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 13 publications
5
71
2
11
Order By: Relevance
“…Studies have explored the effectiveness of medical termination of pregnancy after 10 weeks from LMP, and have demonstrated the efficacy and acceptability of regimens of mifepristone and misoprostol. [5][6][7][8][9] Most protocols used for gestational ages above 63 days from LMP require 800 lg vaginal misoprostol in an in-clinic setting, 24-48 hours after the administration of 200 mg mifepristone, with an additional 400 lg vaginal, oral or sublingual misoprostol administered every 3 hours. As clinical research shows, the effectiveness of termination of pregnancy with mifepristone-misoprostol does not suddenly cease at 64 days of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have explored the effectiveness of medical termination of pregnancy after 10 weeks from LMP, and have demonstrated the efficacy and acceptability of regimens of mifepristone and misoprostol. [5][6][7][8][9] Most protocols used for gestational ages above 63 days from LMP require 800 lg vaginal misoprostol in an in-clinic setting, 24-48 hours after the administration of 200 mg mifepristone, with an additional 400 lg vaginal, oral or sublingual misoprostol administered every 3 hours. As clinical research shows, the effectiveness of termination of pregnancy with mifepristone-misoprostol does not suddenly cease at 64 days of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Termination of pregnancy with mifepristonemisoprostol is also used in the late first trimester (10)(11)(12) weeks from LMP) with documented success rates after 9 weeks from LMP being comparable with those achieved at earlier gestations, with some modifications in the protocol. [5][6][7][8][9][10] Previous research has indicated a high correlation between pregnancy dating determined by clinician (based on bimanual examination and history) and that determined by sonography. 11 Women who have a clear idea of the date of their LMP tend, on average, to believe that their pregnancies are slightly more advanced than they are.…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows also efficacy of medical and surgical method is comparable with no statistically significant difference. 8 Efficacy of medical method is 95% in our study which makes medical abortion in later first trimester an effective alternative of surgical method of abortion. Schaff and colleagues also showed no difference in efficacy in relation to gestation, with medical abortion being highly acceptable (91%).…”
Section: Discussionmentioning
confidence: 61%
“…This is different from our study reason being we have given the treatment according to patient's preference. 8 According to ashok et al, medical abortion is as safe and effective as vacuum aspiration at 10-13 weeks gestation. Our study shows also efficacy of medical and surgical method is comparable with no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…More often, late first-trimester MA up to 13 weeks gestation occurs in an inpatient setting with repeated doses of misoprostol until passage of the pregnancy tissue. Failure rates increase with gestational age, as do the number of doses of misoprostol required, time from induction to abortion, risk of needing a surgical procedure, and risk of needing a blood transfusion [43][44][45][46]. Despite these findings, the procedure remains safe with a success rate above 90 %, and patients report it to be a desirable option [41•, 42••, 43-48].…”
Section: Fda-approved Versus Evidence-based Regimensmentioning
confidence: 99%